2008
DOI: 10.1117/12.814532
|View full text |Cite
|
Sign up to set email alerts
|

Influence of line edge roughness (LER) on angular resolved and on spectroscopic scatterometry

Abstract: Scatterometry or optical CD metrology (OCD) has become one of the most common techniques in quantitative wafer metrology within the recent years. Different tool configurations are either available in commercial inspection tools or subject of recent and present research activities. Among these are normal incidence reflectometry, 2-θ scatterometry, spectroscopic ellipsometry and angle resolved Fourier scatterometry. The two latter techniques appear to be promising for future use in semiconductor fabs. Spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…stitching errors) may be larger than the wavelength and roughness induced scatter as described by the formalism presented here is observable. For small structures and small spatial wavelength perturbations, however, no other diffraction orders than the zeroth order exist and other descriptions like the effective layer model [15,16] must be used to account for roughness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…stitching errors) may be larger than the wavelength and roughness induced scatter as described by the formalism presented here is observable. For small structures and small spatial wavelength perturbations, however, no other diffraction orders than the zeroth order exist and other descriptions like the effective layer model [15,16] must be used to account for roughness.…”
Section: Introductionmentioning
confidence: 99%
“…However, this recent treatment was for a 1D structure, which inherently only describes in-plane scatter between the diffraction orders. In realistic investigations of roughness in scatterometry [5,6,15] also out-of-plane scatter has to be included. It will be shown that in the Fraunhofer far-field approximation, the impact of the line roughness is given by a multiplicative term also for 2D structures.…”
Section: Introductionmentioning
confidence: 99%
“…As one example, recent investigations [12][13][14][15] have shown, that even small feature details like line edge roughness (LER) or line widths roughness (LWR) do significantly affect the analysis of scatterometric measurements. To quantify this effect we performed numerical investigations based on finite element (FEM) based rigorous modelling [16].…”
Section: Identification and Elimination Of Reasons For Systematic Offmentioning
confidence: 99%
“…Restricting to resist structures the computation times keep bearable, since the RCWA algorithms converge much faster for dielectric gratings than for conductive ones. The authors of this work presented a first approach to consider true 3D roughness [25]. In that work strongly bearable computation times could be achieved due to a purely periodic modeling of the LER instead of a truly random model.…”
Section: Influence Of Line Edge Roughness On Scatterometrymentioning
confidence: 99%